2018
DOI: 10.3390/aerospace5040104
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Ordinary Least Squares Parametric Model to Estimate the Cost Per Flying Hour of ‘Unknown’ Aircraft Types and a Comparative Application †

Abstract: The development of a parametric model for the variable portion of the Cost Per Flying Hour (CPFH) of an ‘unknown’ aircraft platform and its application to diverse types of fixed and rotary wing aircraft development programs (F-35A, Su-57, Dassault Rafale, T-X candidates, AW189, Airbus RACER among others) is presented. The novelty of this paper lies in the utilization of a diverse sample of aircraft types, aiming to obtain a ‘universal’ Cost Estimating Relationship (CER) applicable to a wide range of platforms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…However, the decision of retrofitting should not take into consideration only the aerodynamic and structural aspects, and it should typically also consider a DOC assessment, for which the method followed at [48] is suggested. A study [49] that has identified a relationship amongst the Cost Per Flying Hour (CPFH) and aircraft design parameters has shown that the two design variables that contribute the most to the CPFH are the maximum specific fuel consumption and the aircraft empty weight; thus, it is almost certain that a winglet retrofit will influence the operating cost of the aircraft.…”
Section: Discussionmentioning
confidence: 99%
“…However, the decision of retrofitting should not take into consideration only the aerodynamic and structural aspects, and it should typically also consider a DOC assessment, for which the method followed at [48] is suggested. A study [49] that has identified a relationship amongst the Cost Per Flying Hour (CPFH) and aircraft design parameters has shown that the two design variables that contribute the most to the CPFH are the maximum specific fuel consumption and the aircraft empty weight; thus, it is almost certain that a winglet retrofit will influence the operating cost of the aircraft.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the long-term maintenance and sustainment costs of airlifters, i.e., 20, 25 or even 30 years from today, is important. There are various sources that can be used to inform the technical decision-makers, including the manufacturers, which can offer insight on the utilisation costs and publicly available research/industry reports, in conjunction with cost analysis and prediction models, i.e., [9]. For example, a report published by the RAND Corporation in 2013 provides, among others, a comprehensive analysis of the sustainment costs of US fleets of Lockheed Martin C-130 [10].…”
Section: New Airlifter Technical Considerationsmentioning
confidence: 99%
“…The study is conducted using ordinary least squares (OLS) regression with the help of R software for various aircraft types, and they aimed to obtain a "universal" cost estimating relationship. Their study has important findings in terms of near-future cost and fleet maturity predictions on various aircraft types including F-16s and F35s (Lappas and Bozoudis, 2018).…”
Section: Introductionmentioning
confidence: 99%